Reduced Morphological Root Features of Anthracnose Infected Cowpeas (Vigna unguiculata (I.) Walp) (2002)
ln a green house experiment to determine the effects of anthracnose disease caused by collectricum lindemuthianum on cowpea, sterilized siols in planting pots were used for planning two susceptible cowpea varieties (Ife Brown and 1782-60). The seedlings were inoculated with the inoculum meal of the pathogen after 3 weeks of planting. The results obtained show that characteristics tan to brown anthracnose symptoms had appeared on the leaves of both varieties after 3 weeks of inoculation, while the roots of the infected cowpeas were observed to be morphologically different from the roots of the uninfected plants. Similarly, infected plants were smaller in size and a marked reduction in their yield IT82f 60 (35%) versus Ife Brown (19%). The reduction of the plant structures and yield of the infected plants was suspected to have been as a result of the anthracnose disease